MASALAH SENJATA NUKLIR DAN MASA DEPAN PERDAMAIAN DUNIA - Yustiningrum, Emilia (Jurnal Penelitian Politik, 2007)
North Korean nuclear arms test has shocked international communityfor the coming up of a new nuclear state Despite the United Nations sanction on nuclear arms test North Korea tried to prove herself against United States political domination on regulating the world nuclear arms However the test has raised thefear on misuse ofnuclear arms particularly among the states in the East Asia region As the result six countries United States Russia Japan China South Korea and North Korea had the idea to sit together on the negotiation table to solve the North Korean nuclear arms named six party talks Unfortunately each of the six party talk s member has different political interest in solving the problem This situation gave comfortable spacefor North Korea to develop their nuclear arms and lived the international community infear ofthe spread ofnuclear arms all over the world.